Pengembangan LKPD IPA dengan Pendekatan Cultural Responsive Teaching Melalui Design Thinking Framework pada Materi Unsur - Tarigan, Oktaviyani Br; Siskuntoro, Yoyok Hadi (STKIP HARAPAN BIMA, 2024)
This research aims to develop a Science Student Worksheet (LKPD) with a Cultural Responsive Teaching (CRT) approach through a Design Thinking Framework on elemental material. This research method uses Design and Development (DD) with the Design Thinking Framework which consists of five principles, namely Empathize, Define, Ideate, Prototype, and Test Evaluate. The population of this study was class VIII students at one of the junior high schools in the city of Bandung using the Non-Parametric Kolmogorov Smirnov One Sample Test with a total of 31 students. This research instrument is in the form of a validation sheet. The data analysis technique used in this research is the validity test. The results of this research show that the validation data obtained a validity percentage of 3.24 which is included in the valid criteria. This shows that the LKPD with the CRT approach that has been developed is quite effective as a support in the learning process on elemental material.